Complete mitochondrial genome of the four-lined snake, Elaphe quatuorlineata (Bonnaterre, 1790) - Daniel Jablonski; Katarina Soltys; Evgeniy Simonov (Mitochondrial DNA. Part B. Resources, 2019)
Here, we present complete mitochondrial genome of the four-lined snake, Elaphe quatuorlineata (Bonnaterre, 1790) and its comparison with closely related E. sauromates (Pallas, 1814). The complete sequence of the mitogenome is 17,183 bp long and consists of 13 protein-coding genes, two rRNA and 22 tRNA genes, and two control regions. It possesses the same gene order as other mitogenomes of Elaphe spp. and the base composition is as follows: 35.0% (A), 26.7% (C), 25.6% (T), and 12.7% (G), with an A + T bias (60.6%). The presented mitogenome will provide new data for phylogenetic analysis within phylogenetically close western Palearctic species of the genus Elaphe.